Percentage of Rotavirus infection in stool of pediatric patients at Children Welfare Teaching Hospital in Baghdad - Abdul Sattar, Ban A.; Al-Kareemi, Khalida K.; Jassim, Ateka A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Gastroenteritis is a common illness in pediatric age group; the causes could be bacterial, fungal or viral infection. Rotavirus is the most common cause of infectious diarrhea in children. Children between 3 months to 2 years old have the most severe symptoms. Rotavirus is extremely easy to catch and is transmitted mainly by the oral- fecal route. For diagnosis; the specimen of choice is the stool which has been collected during the first 3 to 5 days of illness. If collected 8 or more days after onset of symptoms the specimen will rarely contain the virus.Objective: The objective of this study includes a survey for Rotavirus that cause diarrhea in children admitted to Children Welfare Teaching Hospital in Baghdad between 13th. of Juanuary-2010 to 14th.of October-2010 using a rapid test method for detection of Rota virus to children from one day to 6 years.Materials and Methods: Latex agglutination test for the stool of 61 children suspected with Rotavirus infection was done in addition to general and bacteriological test of these stool samples at Children Welfare Teaching Hospital from January 2010 to October 2010Results: There were 61 children from one day-6 years old, only 11(18.03%) had positive Rotavirus infection with high percentage in males (seven cases) and (four cases) in females and only one case detected with positive Rotavirus infection at the age of 42 month. No pathogenic bacteria or fungus were isolated.Conclusion: The data indicate that male has highly incidence than female and children up to 78 months had diarrhea that not caused by Rotavirus.